Association between polymorphisms in NOS3 and KCNH2 and social memory - Henningsson, Susanne; Zettergren, Anna; Hovey, Daniel; Jonsson, Lina; Svärd, Joakim; Cortes, Diana S.; Melke, Jonas; Ebner, Natalie C.; Laukka, Petri; Fischer, Håkan; Westberg, Lars (Frontiers in Neuroscience, 2015)
Social memory, including the ability to recognize faces and voices, is essential for social relationships. It has a large heritable component, but the knowledge about the contributing genes is sparse. The genetic variation underlying inter-individual differences in social memory was investigated in an exploratory sample (n=55), genotyped with a chip comprising approximately 200.000 single nucleotide polymorphisms (SNPs), and in a validation sample (n=582), where 30 SNPs were targeted. In the exploratory study face identity recognition was measured. The validation study also measured vocal sound recognition, as well as recognition of faces and vocal sounds combined (multimodal condition). In the exploratory study, the 30 SNPs that were associated with face recognition at puncorrected<0.001 and located in genes, were chosen for further study. In the validation study two of the SNPs showed significant associations with recognition of faces, vocal sounds, and multimodal stimuli: rs1800779 in the gene encoding nitric oxide synthase 3 (NOS3) and rs3807370 in the gene encoding the voltage-gated channel, subfamily H, member 2 (KCNH2), in strong linkage disequilibrium with each other. The uncommon alleles were associated with superior performance, and the effects were present for men only (p<0.0002). The exploratory study also showed a weaker but significant association with (non-emotional) word recognition, an effect that was independent of the effect on face recognition. This study demonstrates evidence for an association between NOS3 and KCNH2 SNPs and social memory.